Língua Tikuna: variações na tríplice fronteira Brasil, Peru e Colômbia - Serra (Mecüracü rü Tchai’erucü), Bernabé Bitencourt (2018)
This dissertation discusses internal linguistic variation within the Tikuna language and focuses on the following points: How might we discover the lexical, phonetical and phonological particularities in the Tikuna language spoken in the triple frontier Brazil, Peru, and Columbia? How does one deal with the different forms of speaking of a tonal language, as is Tikuna? Once we understand that languages are not static nor homogeneous, how will one discover the relevant variants in a society as complex as the Tikuna, which has one of the largest Indigenous populations (if not the largest) in Brazil and who live on the largest stretches of territories in the north of Brazil? What variables come to play, in relation to the Tikuna language, on the triple frontier? Do these variables hold any relation to the variables of the Tikuna language distant from the triple frontier, within each of the three countries involved? To begin to answer these questions, we chose three Tikuna villages, in the triple frontier: Bella Vista Callaru (Peru), Arara (Colombia) e Umariaçu I (Brazil). As a starting point, we understand that linguistic variables are a normal phenomenon and a part of the linguistic system itself. This choice is accompanied by the acceptance of the notion of heterogeneity and exists within a concrete historical, social and plural form. The Tikuna people are presented, most of the time, through the inner eyes of its people. To make their way of being and their concepts clearer, we search for elements that may explicit the understanding, further ahead, of the linguistic variables and may better highlight a comprehension and recognition of the people and of their internal alliances, and the affinities shared among the group members. The analysis and interpretation of the data collection are accompanied, in this dissertation, by the intent of creating an awareness of linguistic variables and its role in the Tikuna schools.